The random walk behaviour of Malaysian stock market: evidence from individual stocks - Lim, Kian Ping; Mathew Vun; Lee, Hock Ann (2006)
This study re-examines the price behaviour of 77 individual stocks listed on Bursa Malaysia in light of the random walk hypothesis. With a new statistical tool, namely the Brock-Dechert-Scheinkman( BDS)test, it is possible to detect a more complex form of dependencies in series of financial returns that often appear completely random to standard statistical tests, such as serial correlation tests, runs test, variance ratio test and unit root tests. Our econometric results reveal that the market in general as proxied by the KLCI and all the 77 individual stocks do not follow a random walk process. This conclusion holds even when the sample period is broken down into two sub-periods with the exception of five stocks- IOICorp, KLK, MUllnd, Pos Hldgs and Tchong. The price behaviour of these five stocks in the sub-periods before and during the crisis provides empirical support to our conjecture that the Asian financial crisis in 1997 adversely affected the market's ability to price stocks efficiently, thus preventing stock prices from following a random walk process.